Train noise influence to insomnia level of residents living alongside railway in Gilingan Surakarta - Pujiyanto, Hanif Nugra; Wulandari, R. Aj. Sri; Randita, Amandha Boy Timor (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background Noise is one of the most disturbing environmental hazards in the world. Exposure to noise can cause health problems such as insomnia. Train is one of the transportation which can cause noise in the surrounding area. At Gilingan Surakarta many people live in the area around the railway, which is certainly have potential negative impact from the train noise to health, such as insomnia. Methods: This study was observational analytic with cross sectional study approach. Respondents were selected by simple random sampling method. Measurement of train noise was using the Sound Level Meter. The sample was 90 Surakarta Gilingan residents that were divided into 3 areas of noise. Respondent data retrieval is done by filling preliminary questionnaire which consisted of identity and informed consent, a questionnaire Lie - scale Minnesota Multiphasic Personality Inventory ( LMMPI ) to determine the honesty of respondents, and the questionnaire Insomnia Rating Scale to measure the degree of insomnia respondents. Statistical analysis using the Kruskal - Wallis test. This study aims to determine train noise influence to insomnia level of residents living alongside railway in Gilingan Surakarta. Results: In all of the area was found that noise level exceeds the standard noise level for housing and residential areas that was determined by the Ministry of Environment. In the area I, was found that the average noise level was 82.6 dB , while for area II was 72.8 dB, and area III was 57.1 dB. The result of the Kruskall-Wallis test for insomnia level was 0.42 that means among the three groups did not have statistically significant differences. Conclusions: There was no significant influence of train noise to the insomnia level of residents living alongside railway in Gilingan Surakarta. Keywords: train noise, insomnia level